Pulp revascularization of immature necrotic permanent teeth: An integrative review (Research, Society and Development, 2024)
Pulp revascularization has significant advantages over traditional techniques. While conventional methods, such as obturation, focus on containing the problem by removing the pulp and sealing the canal, revascularization seeks to preserve as much healthy tissue as possible and stimulate biological regeneration. Therefore, the study aims to conduct a literature review on pulp revascularization of immature necrotic permanent teeth. Pulp revascularization of immature necrotic permanent teeth is a regenerative approach that promotes apical closure and continued root development, in addition to restoring pulp functionality. Therefore, scientific research correlates this technique with promising clinical results, highlighting its advantages over traditional methods, such as apexification, by providing a less invasive and biologically oriented approach. Despite significant advances, the technique still faces challenges, such as standardization of protocols and reduction of adverse effects associated with the use of intracanal medications. Future studies should explore approaches that balance efficacy and safety, in addition to investigating the impact of individual variables, such as age and initial condition of the tooth. Thus, revascularization may consolidate itself as the main choice for teeth with this condition, contributing to better clinical prognoses and expanding the arsenal of regenerative techniques in modern endodontics.